The Last Two Decades of Civil-Military Relations in Turkey Under the Shadow of Courts - Ayşegül K. Kaynar (European Journal of Turkish Studies)
The article examines the establishment of civilian supremacy and presidential control over the Turkish Armed Forces in the last two decades. It purports that such control was possible due to the combined use of reformative and repressive instruments. Under the JDP governments, intermittent legal reforms trimmed the political power of military bureaucracy and subjected it to the supervision of civilian administration. At the same time, the military was repressed through criminal prosecutions that affected scores of military personnel. In that way, the article supports the claims that authoritarian transformation of Turkey does not follow a sequential process where years-long reforms were replaced by repression in the state of emergency rule that declared in the aftermath of the July 15 coup attempt. Rather, the JDP deployed reform and repression in a concomitant and complementary way. In fact, repression of military officers through criminal investigations and court cases had never disappeared, even at the height of reforms. In this regard, the article addresses the July 15 attempted coup case and the Ergenekon and Sledgehammer cases separately due to the disparate political/legal contexts surrounding these prosecutions. It also aims to provide an analytical frame for examining judicialized repression in the form of criminal prosecutions.